The inheritance of phenotype character on chickens (Gallus g allus domesticus, Linnaeus 1758)derived from crosses between backross first generation chickens(BC1) - Daryono, Budi Setiadi; Muamar, Arif (2013)
There have been many efforts made to improve quality and develop local chicken as a source of meat for the Indonesian society. One of the efforts being made to increase the growth of local chickens were crossbreed between Pelung chicken with broiler chicken.Pelung chicken cross the parents tock broiler chicken showed that the F1 hybrid has a phenotypic character chicken with a good weight, but the character fenotip still not uniform. Therefore carried out cross-breeding (backcross) between the parent F1 with Pelung chicken both males and females, but the character of the phenotype of the chicken (BC1) is also not uniform yet. Therefore,in this study the selection and development of chickens was conducted by mating BC1 with BC1 to produce a local chicken with a stable phenotype and genotype. Chicken breeders (BC1) males and females were maintenanced in semi-intensivecage KP4, Kalitirto, Berbah, Sleman, Yogyakarta. BC1 chicken crossed with each other and after laying eggs, hatching was done naturally by the breeding female BC1. Chicks (DOC)that have been separated from the stem females were hatched and placed in a special enclosure for maintenance chicks. Chicken weight measurements was performed every week after hatching using digital scales. Then color of his fur, the overall height, weight, tibia,thighs, wings, back, neck and beak were observed at the end of weeks 7. The results showed that the qualitative character of the chicken phenotype (BC 2) from crosses between the members of BC1 chicken feathers produce color dark brown and light brown. The beak all colors are yellow, while the legs are all black color grayish. All forms was single comb and red. Based on survey results revealed that the BC2 chic ken weight of 563.83 ± 109.527. These results suggest the chicken body weight lower than parents of BC2(BC1), which has a weight of 811.625 ± 116.627 in weeks7. Based on these results, it could be concluded that crossing a fellow BC1 chicken will produce BC2 chicken weight lower than BC1 sires, but the characters have a uniform phenotype